DESIGN OF AN AUTOMATIC BRACKISH WATER FILLING SYSTEM IN A COLLECTING TANK FOR AIRPORT WATER MANAGEMENT - Rio Rizko (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2026)
This study develops an automated brackish-water filling prototype for airport clean-water management at Jenderal Ahmad Yani Airport in Semarang. The existing manual filling process required technicians to continuously monitor water levels and operate the pump switch, resulting in inefficiency and an overflow risk. A Research and Development (R&D) approach using the Waterfall model (Analysis, Design, Implementation, and System Testing) was applied. The prototype integrates two water level sensors connected to an Outseal PLC V5 microcontroller and a relay to automatically control a submersible pump. When the lower sensor detects minimum water level, the pump activates; when the upper sensor confirms the tank is full, the pump stops automatically. Expert validation by three validators yielded an overall feasibility score of 86%, categorized as